TO DETERMINE THE EFFICIENCY OF POLYAERYLAMIDE AND PVP AS DRAG REDUCING AGENT IN WATER FLOW SYSTEM - SALLEH, NURUL FADHILAH (2012)
WATERFLOODING IS CLASSIFIED AS SECONDARY RECOVERY YIELDS A SECOND BATCH OF OIL AFTER A FIELD WAS DEPLETED BY PRIMARY PRODUCTION. WORKING ON A WATER OIL IMMISCIBILITY CONCEPT, THE WATER FROM INJECTION WELLS WILL PHISICALLY SWEEP THE DISPLACED OIL TO ADJACENT PRODUCTION WELLS. THIS STUDY AIMS TO PERFORM AN EXPERIMENTAL ANALYSIS TO DETERMINE THE EFFICIENCY OF POLYACRYLAMIDE (PAM) AND POLYVINYLPYRROLIDONE (PVp_ AS DRAG REDUCING AGENT BY MANIPULATING THE REYNOLDS NUMBER, POLYMER CONCENTRATION AND POLYMER DEGRADATION AS THE VARIABLE PARAMETER.